Stimulus‐Responsive Short Peptide Nanogels for Controlled Intracellular Drug Release and for Overcoming Tumor Resistance. Issue 7 (2nd February 2017) - Lyu, Linna; Liu, Fang; Wang, Xiaoyong; Hu, Ming; Mu, Jing; Cheong, Haolun; Liu, Gang; Xing, Bengang
Abstract: Multidrug resistance (MDR) poses a major burden to cancer treatment. As one important factor contributing to MDR, overexpression of P‐glycoprotein (P‐gp) results in a reduced intracellular drug accumulation. Hence, the ability to effectively block the efflux protein and to accumulate the therapeutics in cancer cells is of great significance in clinical practice. In this work, we successfully developed a smart stimulus‐responsive short peptide‐assembled system, termed as PD/VER nanogels, which synergistically combined the acid‐activatable antitumor prodrug doxorubicin (Dox) with the P‐gp inhibitor verapamil (VER) for reversing MDR. Systematic studies demonstrated that such an inhibitor‐encapsulated nanogel could effectively enhance the accumulation of Dox in resistant cancer cells, thereby revealing significantly higher antitumor activity compared to free Dox molecules. This work showed that the assembly of bioactive agents with a synergistic effect into nano‐drugs could provide a useful strategy to overcome cancer drug resistance. Abstract : Strategy to overcome resistance : A smart stimulus‐responsive self‐assembled system (PD/VER nanogel) from a short peptide‐Dox conjugate and P‐glycoprotein inhibitor (Verapamil) has been developed for controlled drug release and simultaneous inhibition of the P‐glycoprotein function to reverse multidrug resistance in cancer cells. This novel system provides a useful strategy to overcome drug resistance for improved antitumor treatment.